2014
DOI: 10.1111/pace.12500
|View full text |Cite
|
Sign up to set email alerts
|

Left Axillary Pacemaker Generator Implantation with a Direct Puncture of the Left Axillary Vein

Abstract: The left axillary generator implantations may reduce the mental burden and cause no safety concerns, and may be performed if functional or cosmetic outcomes are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…They reported that left axillary pacemaker implantation may be performed safely if functional or cosmetic outcomes are required by the patient. 4 ith the advent of optimal biphasic waveform, highershock energy devices, inadequate safety margins for defibrillation have become uncommon. Nevertheless, post-implant defibrillation testing occasionally reveals a high defibrillation threshold (DFT) at which the reliability of defibrillation might be questioned.…”
Section: Article P 878mentioning
confidence: 99%
“…They reported that left axillary pacemaker implantation may be performed safely if functional or cosmetic outcomes are required by the patient. 4 ith the advent of optimal biphasic waveform, highershock energy devices, inadequate safety margins for defibrillation have become uncommon. Nevertheless, post-implant defibrillation testing occasionally reveals a high defibrillation threshold (DFT) at which the reliability of defibrillation might be questioned.…”
Section: Article P 878mentioning
confidence: 99%
“…A detailed description of the cardiac device implantation during the left axilla procedure can be found elsewhere 7 and we utilized the same technique for implanting the TV-ICD. First, patients were placed in the supine position and the left arm was elevated and bent with the patient gripping the handle overhead to expose the left axillary fossa and the lateral margin of the greater pectoral muscle.…”
Section: Implantation Procedures and Patient Follow Upmentioning
confidence: 99%
“…We previously demonstrated that a left axillary pacemaker generator placement with a direct puncture of the left axillary vein is one of the alternatives for a pacemaker implantation. 7 Although the TV-ICD implantations in the left axilla have been described in some case reports and patient series, the number of implants and length of the follow-up have been very limited and most focused on the procedure feasibility or related complications and not on a comparison with the conventional TV-ICD implantation site. [8][9][10][11][12] Thus, we evaluated the safety and feasibility of implanting a TV-ICD in the left axilla and the lead performance data during the long-term follow up and compared it to that obtained with the conventional TV-ICD implantation site (i.e., the left anterior chest).…”
Section: Introductionmentioning
confidence: 99%